Effectiveness of SETS-Based Electronic Student Worksheet (E-LKPD) to Improve Student Learning Outcomes - Mega Indah Puspita Sari; Asri Widowati; Insih Wilujeng; Siti Fatimah Az-Zahro; Desi Ramadhanti (Pendidikan Kimia Unimus, 2022)
This research aimed to determine the effectiveness of electronic-based student worksheets (E-LKPD) on student learning outcomes. The method used was a quasi-experiment with one group pretest-posttest design. The sample taken in a cluster random sampling were 32 students of class VII SMPN 2 Ngemplak Sleman School Year 2021/2022. The instrument used was a problem sheet in the form of a description. The results of the study were analyzed using quantitative descriptive methods. The results of the analysis of the increase in the pretest and posttest obtained an average of N-Gain 0.60 in the medium category. The average pretest value was 6.94 while the average posttest value was 8.80. Test results of t sig value (2-tailed) < 0.05 showed a significant improvement between pre-test and post-test. This indicated that E-LKPD-based SETS was effective for improving students' cognitive learning outcomes.